Electricity biogeneration using microbial fuel cells approach - Wahid, Herman; Razali, Halimatus Saadiah; Zolkipli, Muhammad Faris Al Hafiz; Zamri, Muhammad Zulhafiz (Penerbit UTHM, 2020)
Renewable energies are very important because they released clean gasses to the atmosphere. Hence, polluted air and water can be prevented by using renewable energy sources to generate power. Nowadays, primary fuel sources, especially fossil fuels, are used in generation of the electric energy. However, generation of electricity by using these fuel sources gives negative effects on the environment and human health. It is because the power plants will release substances for air pollution such as carbon monoxide (CO), nitrogen oxide (NOx) and also sulphur dioxide (SO2). Besides, Greenhouse gases (GHGs) was produced when the fossil fuels are burned. It will lead to climate changes and degrade the environment...